(untitled) (Journal of Medical & Health Sciences Review, 2025)
Cutaneous leishmaniasis is one of the infectious diseases which present in most of the countries included Pakistan. It transmits by the bite of infected female phlebotomine sandflies. Cutaneous Leishmaniasis is a considerable health problem in Karak District of Kohat Division. The presence of secondary bacterial infection in cutaneous Leishmaniasis wound aggravates the lesion and delays the healing process of Leishmaniasis wound. The present study was aimed at isolating and identifying the bacteria from leishmaniasis wound and checking the antibiotic sensitivity pattern. The current study was conducted on the 50 patients having clinical feature of leishmaniasis. Wound samples were collected through sterile swab from patients. After microscopically confirmed samples (Giemsa stain) were cultured on different bacteriological media (Nutrient agar, Blood agar and MacKonky agar). The colorless colonies were subjected to biochemical identification such as Gram staining, oxidase, Triple sugar iron (TSI), Methyl red (MR) and Vogues Prousker (VP) to identify potential bacterial isolates. The identified bacteria were subjected to antibiotic sensitivity test, carried out by disc diffusion method on Nutrient agar. The main isolated pathogens in this study were Escherichia coli, Klebsiella species (Gram negative) and S. aureus (Gram positive). Most of the isolates showed resistance against some antibiotics such as penicillin and ceftriaxone and some isolates showed intermediate susceptibility to tested antibiotics.